Analysis of Implementation of PSAK Number 109 Accounting at The National Amil Zakat Board Makassar City - Zakariah (JEKAMI Journal of Accounting, 2021)
This study aims to determine the suitability of recognition, measurement, presentation and disclosure of PSAK No. 109 at the Makassar City National Amil Zakat Board. This type of research is descriptive qualitative, the type of data used is primary data in the form of data obtained directly from first party sources. This study used a comparative descriptive data analysis technique by comparing the accounting standard statement No. 109 with the financial statements at BAZNAS Makassar City. The results of the analysis show that in the process of recognition, measurement, and presentation, Makassar City BAZNAS is in accordance with PSAK No. 109. However, there are a few things that are not in accordance with the disclosure in PSAK No. and a ZIS receiver.